Decomposition prevention through thermal sensitivity of hydrate formations around wellbore. (August 2019) - Wei, Jia; Cheng, Yuanfang; Yan, Chuanliang; Li, Qingchao; Han, Songcai; Ansari, Ubedullah
Highlights: The decomposition rate model of hydrate is improved to consider salt invasion. Thermal sensitivity is so high that it totally offsets pressure sensitivity's effects. Heat and salt convection caused by high bottomhole pressure destabilize wellbore. Raising drilling fluid density conventionally can bring reverse effects. Latent heat decreases temperature in the entire formation due to heat transfer. Abstract: The traditional drilling engineering research on wellbore stability of hydrate formation neglects the interactions between heat transfer and mass transfer, a new multi-field coupling model is established to study the effects, and this model considers hydrate kinetic decomposition rate in different salinities, two-phase flows and heat transfer in pores. The calculation results show most of engineering parameters affects hydrate decomposition through high thermal sensitivity of hydrate formations: The direction and value of seepage will change the temperature field and the position of hydrate dissociation front. High bottomhole pressure will bring in the radial seepage, increasing formation temperature and exacerbating hydrate decomposition. The latent heat of hydrate dissociation reduces temperature growth in the entire formation, inhibits the decomposition front advancement and decreases the decomposition rate. Reducing the bottomhole temperature can get an incremental margin for wellbore stability. High salinity in drilling fluid will provide negative impact under high bottomhole pressure and high permeability. These results show the protection of hydrate formations should avoid increasing the density of drilling fluid and focus on cooling drilling fluid and reducing drilling time.